Literature Review: Potensi Kombinasi Pijat dan Aromaterapi Lavender Terhadap Kualitas Tidur Bayi - Mega Karina Putri; Melia Eka Rosita; Andina Vita Sutanto (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Factors that affect the growth of the baby is the fulfillment of sleep needs, 75% of growth hormone is excreted when the baby sleeps, so it can stimulate brain development. However, babies often have difficulty sleeping due to various factors. Many studies have proven that massage using lavender aromatherapy has succeeded in improving the baby's sleep needs. Therefore, to summarize the results of this study, a literature study was carried out on the effect of lavender massage and aromatherapy. Literature review was carried out by searching scientific articles with keywords: aromatherapy-baby massage, aromatherapy massage on babies, baby massage and aromatherapy on babies. Article searches were performed on PubMed and Google Scholar. The search results obtained 7 articles that met the inclusion criteria. Based on the results of the literature review, it can be seen that the study population involved were infants aged 0-12 months. Baby massage combined with lavender aromatherapy can improve the quality of baby sleep and can affect the length of time to sleep and babies can easily fall back asleep when they wake up. Lavender aromatherapy can provide a calming effect, improve mood, blood circulation, maintain and increase endurance, sedative, hypnotic and anti-neurodepressive effects.